Vaccinations: Mandatory or Voluntary? Risk-Benefit Analysis - Yehoshua Socol; Yair Y. Shaki (SAGE Publishing, 2020)
The discussion regarding mandatory vaccination of children centers mainly around the question of whether producing public good has precedence over the freedom of individuals. In the core of this discussion lies the assumption that mass immunization has been proven as a public good, based on the experts' opinion that there is no proof of significant damage caused by vaccinations. We suggest, however, that this argument is insufficient. Namely, beside acute effects, vaccination (as any intervention) can shorten long-term life expectancy. If, for example, vaccination is intended to prevent an illness that causes 0.05% mortality or permanent disability population-wide (like in the case of measles), the population-wide vaccination can be considered as a public good only if the vaccination itself does not cause life shortening by 0.05%, that is, by about 15 days. Absence of such a small long-term effect has not been proven and cannot be proven in principle for several decades to come. The lack of proof of damage is not proof of lack of damage; in any dispute, the burden of proof lies with those who lay charges. Therefore, we conclude that it is inappropriate today to enforce mandatory immunization.